The Federal Democratic Republic of Ethiopia : Selected Issues and Statistical Appendix. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
This Selected Issues paper on The Federal Democratic Republic of Ethiopia highlights that accelerating private sector development is the key to increasing and sustaining growth, and providing employment opportunities to raise incomes. Private sector development remains in its infancy, reflecting the slow transition to a market economy, and the contribution of industry to GDP has not changed significantly. The World Bank has identified some key areas to improve the investment climate, which include deeper financial sector reform and acceleration of the privatization program.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet